Pulmonary Langerhans Cell Histiocytosis - Shaw, Brian; Borchers, Michael; Zander, Dani; Gupta, Nishant (Seminars in Respiratory and Critical Care Medicine, 2020)
Pulmonary Langerhans cell histiocytosis (PLCH) is a diffuse cystic lung disease that is strongly associated with exposure to cigarette smoke. Recently, activating pathogenic mutations in the mitogen-activated protein kinase pathway have been described in the dendritic cells in patients with PLCH and have firmly established PLCH to be an inflammatory myeloid neoplasm. Disease course and prognosis in PLCH are highly variable among individual patients, ranging from spontaneous resolution to development of pulmonary hypertension and progression to terminal respiratory failure. A subset of patients with PLCH may have extrapulmonary involvement, typically involving the skeletal system in the form of lytic lesions, skin lesions, or the central nervous system most commonly manifesting in the form of diabetes insipidus. Smoking cessation is the cornerstone of treatment in patients with PLCH and can lead to disease regression or stabilization in a substantial proportion of patients. Further insight into the underlying molecular pathogenesis of PLCH has paved the way for the future development of disease-specific biomarkers and targeted treatment options directed against the central disease-driving mutations.
Keywords: PLCH; pneumothorax; MAPK; BRAF; cladribine; smoking